Investor as Homo Oeconomicus or Human; What Deviates Financial Market Decisions from Rationality? : - Vacha, Robert (2017)
The thesis deals with the differences among phenomena of Homo Oeconomicus and Human and their presence in the financial markets. Furthermore, it aims at revealing differences of behavior in alignment with the phenomena among groups of people involved and not involved in the financial markets. To do so we use an experiment with its assessment based on the Anchoring Index. For the purpose of the research of behavior in alignment with the Prospect theory, the thesis defines new index of assessment of human behavior the Human Index upon which it draws conclusions about the two groups. The results show no significant difference in propensity to bias and marginal difference in behavior in alignment with the prospect theory where the group involved in the financial markets reveals less Human behavior. Altogether, the findings are no remarkable difference in behavior among the two groups, i.e. both the group of people involved in the financial markets as well as those not involved are Human at very similar levels.